ENVIRONMENTAL ASPECTS OF MODERNIZATION OF HIGH POWER WATER-HEATING BOILERS - P. M. Glamazdin; D. P. Glamazdin; Yu. P. Yarmolchick (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
Boilers of KVGM and PTVM series are characterized by high values of NOx and CO content in the combustion products. Reduction of NOx and CO content can be achieved by two ways: by installing the condensing heat recovery unit at the boiler outlet and by improving the heat and mass transfer processes in boiler furnaces. Application of the condensing heat recovery units causes pollution of resulting condensate by low-concentration acids. The authors conducted a study in order to determine the effectiveness of the previously applied methods of suppressing the emission of nitrogen oxides in the boilers of these types. Equalization of the temperature field and, consequently, enhancement of heat transfer in the furnace by substitution the used burners by the more advanced ones, the design of which facilitates reduction the emission of nitrogen oxides, were applied to all the upgraded facilities. The studies fulfilled demonstrate that a reduction of NOx emissions in water-heating high power boilers is fairly possible by means of modernization of the latter. The authors have developed the project of the PTVM-30 boiler modernization, which was implemented at a large boiler plant in the city of Vinnitsa (Ukraine). The project included a number of technical solutions. Six burners were replaced by the two ones that were located in the hearth; also the hearth screen was dismantled. At the same time, reducing the total surface area of the heating caused by the exclusion of hearth screen was compensated by filling the locations of the six embrasures of staff burners on the side screens with straightened furnace tubes. Installing the burners separate from the screen made it possible to eliminate the transfer of vibration to the furnace tubes, and – via them – to the boilers setting. Automation provided “associated regulations”. Draught machines were equipped with frequency regulators. During commissioning of the boiler the studies were carried out that related to the identification of dependency of the emission level on the shape of the temperature field in the furnace, in particular, – on the intensity of twist of gas-air mixture at the exit from the burner. We studied two extreme cases, i.e. the case of the maximum achievable level of burner twist that is equal to 45° and the case of no twist. As a result of experiments, it was observed that if a decrease of the twist rate takes place the emission of nitrogen oxides is reduced. The methods of further reduction of emissions of nitrogen oxides have been determined, viz. the device recirculation of flue gases by mixing them in a blast air; conducting the process at low excess of air with controlled chemical underburning when complete oxidation of carbon to CO2 accomplishes outside the furnace at the initial section of the convection part; hydration of blowing air into the humidification amount of 1.5–2.0 % of the nominal output of the boiler.